'A human values issue': Actors, arguments, and regulatory change in the Florida land‐based shark fishery. Issue 12 (7th November 2022) - Wester, Julia; Turffs, Dylann; Shiffman, David; Macdonald, Catherine
Abstract: Recreational shark fisheries have been the subject of recent public attention because of the possible impacts on shark populations and conflicts between stakeholders. A case study is presented based on discussions that took place in summer 2018 about potential changes to policies regulating recreational land‐based shark fishing in Florida. Comments from public meetings and workshops (totalling 15.8 hours) and online comments (1, 050) submitted to the Florida Fish and Wildlife Conservation Commission (FWC) were analysed using the lens of actor–network theory. The case study explores the intersection of conflicting stakeholder interests and types of knowledge, including how stakeholders variously defined the problem of user conflict in a coastal public space, and how they aligned themselves in relation to the problem and to each other. It further illustrates how shifting values and norms can intersect with changing technologies and environmental realities to produce new or increasing conflicts between natural resource user groups. This study underlines the importance and potential benefits of regulatory agencies explicitly and transparently engaging with value trade‐offs when managing conflicts among users of natural resources.